Effect of Different Primary Processing Methods on Flavor Compounds and Sensory Characteristics of Coffee Beans - Ke XIAO; Huinan ZHAI; Rongsuo HU; Xinxin YU; Wenjiang DONG (Shipin gongye ke-ji)
The objective of this study was to investigate the effects of different primary processing methods on the physicochemical properties, flavor and sensory characteristics of Arabica coffee. The sensory flavor of coffee samples from different primary processing methods were evaluated by E-nose and sensory evaluation, principal component analysis (PCA) was used to differentiate different primary processing methods, and Pearson's correlation coefficients were used to analyze the relationship between the primary processing methods and the flavor compounds produced. The results showed that in terms of physicochemical indexes, different primary processing methods had significant (P<0.05) effects on total titratable acidity (TA), total soluble solids (TSS) and pH value of the coffee samples, with wet processing (CS) having the highest pH value. Primary processing methods had a significant effect on the content of flavor compounds such as alkaloids, chlorogenic acid and organic acids in the coffee samples, with dry processing Ⅰ (GA) having the highest caffeine (12.32 mg/g DW), honey processing Ⅰ (MA) having the highest fenugreek (3.71 mg/g DW), and wet processing (CS) resulting in coffee samples having the lowest chlorogenic acid and the highest organic acid. In addition, the E-nose results showed that the contents of aroma compounds of coffee prepared by different primary processing methods were significantly different, and the E-sensory analysis could be more effective in distinguishing different primary processing methods than manual evaluation. The results of this study clarified the effects of different primary processing methods on the chemical composition and sensory flavor of coffee, which was of great importance for the enhancement of coffee flavor quality and the classification and identification of high-quality products.